(untitled) (Research, Society and Development, 2021)
Through this scientific material, we draw a study of old age with regard to sexuality, and we list body and pleasure as descriptors, so discussed in the scope of philosophy and psychoanalysis. In this sense, our goal is to conduct a review of the literature on old age and sexuality in postmodernity, through a study that encompasses the body and pleasure. Our thinking is instituted by means of the following statement: unlike what some common sense prejudices say, old age is not synonymous with functional disability, dependence or absence of social and sexual experiences. We are anchored, therefore, in the line of thought that emphasizes the need to rescue the right to a sexual life in old age, since it implies being able to think about love in its libidinal transformation forms. Finally, we emphasize that it is necessary to understand it in a wide range, which includes tenderness, physical contacts that erogenize the body, such as the look, the voice and the touch.